DESKRIPSI JAMUR ENDOFIT DARI TUMBUHAN RARU (Cotylelobium melanoxylon) GENUS BOTRYTIS - Uswatun Hasanah; Idramsa Idramsa (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
ABSTRACK This study aims to identify the endophytic fungus from the bark of the plant raru (Cotylelobium melanoxylon). This study uses identification technique manually by viewing and comparing the macroscopic and microscopic morphological characteristics of each isolate endophytic fungi then seek to obtain dendogram similarity index which divides each isolate into several clusters/genus. Data were analyzed using cluster analysis Simple Matching Coefficient in the Multi Variate Statistical Package (MVSP) where each isolate that had ≥70 % similarity indices are grouped into one cluster/genus. The results of cluster analysis to get 8 cluster/genus endophytic fungi found in the bark of plants raru (Cotylelobium melanoxylon). Eighth genus included the genus Alternaria, Aspergillus, Botrytis, Debaromyces, Fusarium, Mycelia sterile, Nigrospora, and Scopulariopsis. This paper presents a description of the genus Botrytis. Kata Kunci: Identifikasi, Jamur Endofit, Cotylelobium Malanoxylon,  Indeks Similiritas